MiR-20a-5p targets RBM24 and alleviates hypertensive intracerebral hemorrhage: MiR-20a-5p alleviates hypertensive intracerebral hemorrhage - Xu, Li; Mo, Chuangqi; Lu, Ming; Wang, Pingping; Liu, Yue (Cellular and Molecular Biology, 2023)
Hypertensive intracerebral hemorrhage (HICH) poses a significant challenge due to its high incidence, mortality, and diagnostic complexities. The underlying molecular mechanisms of HICH development remain enigmatic. In this study, we identified differentially expressed miRNAs in HICH patients by employing miRNA microarray analysis. We found that miR-20a-5p was one of the miRNAs significantly down-regulated in HICH patients and was significantly associated with clinicopathological features of the patients. Subsequently, Human umbilical vein endothelial cells (HUVECs) were transfected with miR-20a-5p mimics or inhibitors to investigate the role of miR-20a-5p in proliferation, apoptosis, migration, and angiogenesis. Similarly, a mimic of miR-20a-5p or its inhibitor was injected into the HICH animal model and measured HICH markers in brain tissue. We next employed a bioinformatic approach to investigate the potential targets of miR-20a-5p which was further confirmed using gain and loss of function assays in HUVECs and animal models. The results show that overexpression of miR-20a-5p in HUVECs enhanced cell proliferation, migration, and tube formation while suppressing apoptosis, and attenuated HICH development in vivo. miR-20a-5p mediated its effects by directly targeting RBM24 and silencing RBM24 could partially recover the suppressive effects of miR-20a-5p on the development of HICH. Interestingly, miR-20a-5p hindered the development of HICH and its influence relied on the HIF1α/VEGFA pathway.